2022
DOI: 10.21608/jtcps.2022.130253.1115
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Natural Dyes Extraction Techniques for Valuable Utilization on Textile Fabrics

Abstract: N ATURAL dyes are colours generated from natural sources. Many chemical processes using petrochemical-based dye intermediates are used in the creation of synthetic dyes, which use a lot of energy and release harmful toxic substances into the environment. So they have been substituted with natural ones that have many advantages, and despite these advantages, natural dyes have some serious disadvantages because of the technical and environmental challenges related to the production and use of natural dyes. To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…[8][9][10][11][12][13] It is also the process of mixing a design concept, one or more colors, and a substrate (usually textiles) with a natural or synthetic thickener while applying a technique to correctly apply the colors. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The main objective of printing is to create colorful patterns with sharp borders on textile fabrics without any dye spilling beyond the design motif's borders. [29] Textile printing is defined as a regulated technique of coloring cloth in specific patterns or motifs by employing specialized printing techniques and machinery.…”
Section: Textile Printingmentioning
confidence: 99%
“…[8][9][10][11][12][13] It is also the process of mixing a design concept, one or more colors, and a substrate (usually textiles) with a natural or synthetic thickener while applying a technique to correctly apply the colors. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The main objective of printing is to create colorful patterns with sharp borders on textile fabrics without any dye spilling beyond the design motif's borders. [29] Textile printing is defined as a regulated technique of coloring cloth in specific patterns or motifs by employing specialized printing techniques and machinery.…”
Section: Textile Printingmentioning
confidence: 99%
“…[8][9][10][11][12] It is also the process of mixing a design concept, one or more colours, and a substrate (usually textiles) with a natural or synthetic thickener, while applying a technique to correctly apply the colours. [4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] The main objective of printing is to create colourful patterns with sharp borders on textile fabrics without any dye spilling beyond the design motif's borders. [27] Textile printing is defined as a regulated technique of colouring cloth in specific patterns or motifs by employing specialized printing techniques and machinery.…”
Section: Textile Printingmentioning
confidence: 99%
“…This is supported by Adeel et al, [10], who reported that natural dyes have gained wide acceptance because they exhibit better biodegradability and more compatibility with the environment, which promotes sustainability in textiles. Additionally, Ragab et al, [11] also mentioned that natural dyes offer numerous medical benefits to the wearer as they are skin-friendly and generally non-hazardous to human health. However, Kumar [12], pointed out that natural dyes have drawbacks and inconsistencies in shades when applied alone without mordants.…”
Section: Introductionmentioning
confidence: 99%
“…However, Kumar [12], pointed out that natural dyes have drawbacks and inconsistencies in shades when applied alone without mordants. As a result, nearly all-natural dyes need the application of mordants to adhere to the textile substrate [11]. Mordants are used to obtain various shades of colours and achieve spectacular performance parameters on textile materials [13].…”
Section: Introductionmentioning
confidence: 99%

Colour Properties of Infrared Bandicoot Berry (Leea Indica) Dyed Silk

Anis Nazahah Mohd Amin,
Nor Juliana Mohd Yusof,
Wan Syazehan Ruznan
et al. 2024
ARASET